MODEL PENDIDIKAN KARAKTER TERINTEGRASI DI SMKN 2 DEPOK SLEMAN YOGYAKARTA - Nur Hamidi (Universitas Ahmad Dahlan, 2013)
Character education is a conscious effort to improve and enhance the entire behavior of students that include values, potential, abilities, talents, and mind. In order for these efforts to be successful in both, must start from the smallest scope. Start of school, community, and family environment in an integrated way. If education is successful, it will be realized that not only generation smart intellectual (cognitive), emotional (effective), but also robust generation of faith, which is not only master the hard skills but also soft skills to master. In the context of Islam, Islam does not allow moral turpitude. Prophet Muhammad was sent in an effort to enhance human morality.